Similarity Among 10 Cayenne Pepper (Capsicum frutescens L.) Mutant Accessions Resulted from Gamma-Ray Irradiation - Asya Zhafira Khairunissa; Makhziah Makhziah; Djarwatiningsih Poengky Soedjarwo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Cayenne pepper (Capsicum frutescens L.) is a horticultural crop which production is not comparable to the level of public consumption. Chili plants induced by gamma irradiation experienced character changes, which caused the population of mutant accessions to have a diversity of characters. The similarity test of mutant accessions was carried out to determine the relationship distance between accessions. The research was carried out at the Faculty of Agriculture, UPN "Veteran" East Java, Surabaya City, with a geographical location at 7⁰ 9' - 7⁰ 21' South Latitude and at 112⁰ 36' - 112⁰ 54' East Longitude. The experimental design used was a Completely Randomized Design, with 3 replications of each, also using one factor, namely mutant ( ) or genotype resulting from gamma ray irradiation mutations of cayenne pepper. Heritability tests were also carried out in this study. The results of the heritability test showed that the characteristics of plant height, fruit length, fruit diameter, fruit weight per plant, and number of fruit per plant had high heritability values, namely above 30%. The result of similarity test visualized by the dendogram shows that 10 mutant accessions and the parental have a similarity coefficient ranging at 21% to 78%. The lowest similarity coefficient is owned by M2 accession, specifically at 21%.